Republic of Belarus : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context: Attempts to boost activity with policy stimulus, in lieu of much-needed structural reform, have failed to raise growth and contributed to large external imbalances. Adverse developments in the region further cloud the outlook. High financing needs and low buffers leave Belarus highly dependent on external financial support. The risk of disorderly adjustment remains high. Challenges: Mitigating immediate risks and facilitating external adjustment through a sharp change in macroeconomic policies. Advancing the transition to a market-based economy to raise sustainable growth. Policy recommendations: -- Halt wage increases and reduce subsidized lending to slow demand growth; -- Reduce foreign exchange interventions and tighten monetary policy to facilitate external adjustment; -- Enhance market orientation of the economy through a rapid phase-out of price controls and mandatory targets and by privatization of state-owned enterprises.